2019
DOI: 10.26555/eshr.v1i1.938
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Dengue in Indonesia: A Systematic Review

Abstract: Background: Climate change is a global issue because of its impact on environmental and human health. No exception for Indonesia, an archipelago state with a tropical climate. Climate change potentially influences the mosquitos borne disease, including dengue fever, which poses a vulnerability to the Indonesian populations. This article aims to review the association and the impact of climate change to dengue fever, particularly in Indonesia and to inform the policymaker on directing the adaptation option.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The prevention of dengue fever is one of the most important aspects of disease control. In locations where a dengue vaccine is available, preventative strategies include vaccination, the elimination of breeding grounds for mosquitoes, the use of insect repellents, the installation of screens and mosquito nets, community-based activities for mosquito control, and the use of mosquito repellents [9]. In order to lessen the toll that this mosquito-borne viral illness has on the general population's health, it is necessary to use a comprehensive strategy for dengue prevention and control [9].…”
Section: Dengue Fever Cause Transmission and Treatmentmentioning
confidence: 99%
“…The prevention of dengue fever is one of the most important aspects of disease control. In locations where a dengue vaccine is available, preventative strategies include vaccination, the elimination of breeding grounds for mosquitoes, the use of insect repellents, the installation of screens and mosquito nets, community-based activities for mosquito control, and the use of mosquito repellents [9]. In order to lessen the toll that this mosquito-borne viral illness has on the general population's health, it is necessary to use a comprehensive strategy for dengue prevention and control [9].…”
Section: Dengue Fever Cause Transmission and Treatmentmentioning
confidence: 99%
“…Climate affects the pattern of infectious diseases because vector and viruses sensitivity for any change that directly or indirectly affect the onset of a disease. Some studies have revealed that there is a significant association between DHF with climatic conditions including air temperature, humidity, and precipitation due to increasing breeding place for of Aedes aegypti as primary vector of dengue virus (Colón-González et al 2013, Fatmawati and Sulistyawati 2019, Xiang et al 2017). Thus, investigation on how the climate variables impact to dengue incidence in Badung could enrich the discussion around this issue.…”
Section: Introductionmentioning
confidence: 99%